Clipper coder - Binarao, Lovella Joy T. (Animo Repository, 1993)
In the aim of having information arranged systematically, databases came into life. The evolving technology of database concepts has resulted in the emergence of database management system packages (DBMS). Today, these products typically include features aimed at helping add to the user's productivity. This is, essentially, the purpose behind this system. Clipper Coder was designed with the goal of developing an add-on program capable of generating Clipper code, based on user specifications of screen displays, menu outlines, report formats, and queries. Specifically, it is directed towards the aim of providing the user with a blackboard-type tool supporting keyboard as well as mouse manipulation, wherein specifications for screens, menus, reports, or queries, may be supplied. From these inputs, the corresponding Clipper code is then generated. The first module, the Screen Painter, handles the creation of screen displays. Various screen interface objects are provided which the user may create and lay out on the screen. The second module, the Menu Builder, allows the user to specify the items that will make up a menu, and then generates the Clipper code to produce the desired result. The third module, the Report Generator, provides a blackboard where text, fields, and groups may be created for the report. Print styles, calculations, and an option to generate code for sending the results to either the printer or a file, are also included. The last module, the Query Builder, accepts input from the Screen Painter and the generates the corresponding query. The result is a querying screen which can handle different combinations of values for the given fields, in order to form the query conditions. In order to integrate the Clipper code generated by these four modules, it is recommends that future work on projects of this nature be focused on the design of a system which integrates input for screens, menus, reports, and queries, in order to come up with a complete, running application.